The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0132987
|View full text |Cite
|
Sign up to set email alerts
|

BTB-Zinc Finger Oncogenes Are Required for Ras and Notch-Driven Tumorigenesis in Drosophila

Abstract: During tumorigenesis, pathways that promote the epithelial-to-mesenchymal transition (EMT) can both facilitate metastasis and endow tumor cells with cancer stem cell properties. To gain a greater understanding of how these properties are interlinked in cancers we used Drosophila epithelial tumor models, which are driven by orthologues of human oncogenes (activated alleles of Ras and Notch) in cooperation with the loss of the cell polarity regulator, scribbled (scrib). Within these tumors, both invasive, mesenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 84 publications
(126 reference statements)
2
40
0
Order By: Relevance
“…While there are clearly differences between Ras85D V12 /scrib −/− and N ACT /scrib −/− tumours, research has also uncovered many genetic similarities between them. Microarray data from Ras85D V12 /scrib −/− and N ACT /scrib −/− tumours has identified just over 500 genes that were similarly misregulated between the two tumours, as well as 103 genes that were specifically responsive to JNK signalling shared between them (Doggett et al, 2015). Four of those genes were BTB-zinc finger TFs, and one of those was chronologically inappropriate morphogenesis (chinmo), which was shown to be capable of cooperating with both Ras85D V12 and N ACT to drive tumourigenesis, even if JNK signalling was blocked (Doggett et al, 2015).…”
Section: Pro-tumourigenic Jnk Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are clearly differences between Ras85D V12 /scrib −/− and N ACT /scrib −/− tumours, research has also uncovered many genetic similarities between them. Microarray data from Ras85D V12 /scrib −/− and N ACT /scrib −/− tumours has identified just over 500 genes that were similarly misregulated between the two tumours, as well as 103 genes that were specifically responsive to JNK signalling shared between them (Doggett et al, 2015). Four of those genes were BTB-zinc finger TFs, and one of those was chronologically inappropriate morphogenesis (chinmo), which was shown to be capable of cooperating with both Ras85D V12 and N ACT to drive tumourigenesis, even if JNK signalling was blocked (Doggett et al, 2015).…”
Section: Pro-tumourigenic Jnk Signallingmentioning
confidence: 99%
“…Microarray data from Ras85D V12 /scrib −/− and N ACT /scrib −/− tumours has identified just over 500 genes that were similarly misregulated between the two tumours, as well as 103 genes that were specifically responsive to JNK signalling shared between them (Doggett et al, 2015). Four of those genes were BTB-zinc finger TFs, and one of those was chronologically inappropriate morphogenesis (chinmo), which was shown to be capable of cooperating with both Ras85D V12 and N ACT to drive tumourigenesis, even if JNK signalling was blocked (Doggett et al, 2015). A similar role was identified for the BTB-zinc finger TF fruitless, while another BTB-zinc finger TF, abrupt, was able to compensate for chinmo removal in driving tumourigenesis of scrib −/− /Ras85D V12 clones (Doggett et al, 2015).…”
Section: Pro-tumourigenic Jnk Signallingmentioning
confidence: 99%
“…The earliest metastasis model involved activated Ras combined with loss of the tumor suppressor scribble (Pagliarini and Xu, 2003). Subsequent studies have identified further factors involved in both Ras and Notch driven tumorigenesis (Doggett et al, 2015). Notch pathway activation coupled with alterations in histone epigenetic marks also lead to a Drosophila tumor model (Ferres-Marco et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous transcriptome profiling by our group and others [11][12][13] has suggested that disturbed cell polarity leads to upregulation of atf3 expression. Consistently, qRT-PCR from scrib 1 homozygous mutant larvae and adult heads bearing dlg1 G0342 homozygous mutant clones showed increased levels of atf3 mRNA ( Fig 1A), thus confirming induction of atf3 transcription upon depletion of the Scrib polarity module.…”
Section: Atf3 Is a Cell-polarity Response Gene Activated By Apkc But mentioning
confidence: 81%
“…The importance of finely tuned Atf3 expression during Drosophila development corresponds with the role of mammalian ATF3 as a stress-response gene regulated at the level of mRNA expression by various stimuli, including genotoxic radiation, wounding, cytokines, nutrient deprivation, Toll signaling, oncogenes and inhibition of calcineurin-NFAT signaling [7][8][9]. Independent transcriptome analyses of Drosophila epithelia have shown deregulated atf3 expression in wing imaginal discs lacking the conserved neoplastic tumor suppressor genes scribble (scrib) or discs large 1 (dlg1) encoding components of the Scribble polarity module [10], and in ras V12 scrib − tumors in the eye/antennal imaginal disc (EAD) [11][12][13]. These results point to loss of epithelial integrity as a novel trigger of atf3 expression and are congruent with studies linking Atf3 to processes involving transient controlled epithelial depolarization during morphogenesis and wound healing [14][15][16] as well as to pathological disturbances in polarity that characterize chronic wounds and tumorigenesis [5,9,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%